Critical Viewpoint on the Obedience of High School Persian Books to the Field of Aesthetics and Art Document of the Fundamental Revolution of Education - Fatemeh Jafari Kamangar; Maryam Zarei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In Iran, a large part of the education and guidance of students is achieved through textbooks, which requires a precise and calculated roadmap to achieve it. The document of fundamental revolution of education has been compiled based on these principles and inspired by upstream documents and according to the strategies of the Islamic Republic, and the authors of textbooks are obliged to present the principles and areas of this document in order to achieve this important goal. The field of aesthetic and artistic education is the sixth field in the section of the theoretical model of educational fields of this document. The statistical population in the present study is Persian high school textbooks and the statistical sample is the Persian textbook of the twelfth grade. Qualitative analysis of the present study was performed by deductive coding and classification of data and the unit of analysis in this study was the sentence. To achieve the reliability of the codes, parts of the book were coded by two coders and its validity was done by the method of pluralism and trust-building. Also, the research atmosphere was controlled with the presence of an external judge. Quantitative analysis of the code was performed by SPSS software. According to the analysis, the frequency of sentences that considered this field was 49.11%, which the amount of attention to its principles is unequal and, in some cases, such as directing educators to a special artistic orientation and creativity, is very little. Authors require textbooks.